Simple PC: driven function generator / Faizah Atan and Norazizah Saad - Atan, Faizah; Saad, Norazizah (1990)
In electronic engineering we often use signal generator that generate certain waveform to test circuit. A knowledge of how a circuits behaves at various frequency will enable us to predict how it will response to a complex input signal. Hence there is a need to have a wave generator which is capable of supplying complex waveforms over a range of frequency with a variable amplitude. Most common signal generator provide a sinusoidal, triangular, sawtooth, and squarewave waveform. In this project all the common waveform can be generated as well as any other complex waveforms that can be dreamt of.